Penanaman Karakter Dalam Pembelajaran Jarak Jauh - Sistriani , Dani (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2021)
During a pandemic, which has an impact on the world of education, which requires distance learning, resulting in the emergence of various problems, including the cultivation of character for students. Therefore it is necessary to have innovation in distance learning that is good and effective, so that it can instill character in students. This paper will provide descriptions related to some of the methods that are carried out, and can be used as a reference for educators in instilling character in students in distance learning during the Corona pandemic that is hitting Indonesia. This research is a descriptive qualitative research. Researchers obtained data from interviews, observations and documentation on 12 teachers at SD NU Master Sokaraja. There are four ways that can be practiced by school educators at the current PJJ period, namely: Integrating character planting in the curriculum, character planting through class management, character building through the choice of methods and the use of learning methods, character building through the literacy movement.